Factors affecting consumers’ purchase intention for agriculture products omni-channel - Liu, Yan; Zheng, Shuyin (Frontiers in Psychology, 2023)
The live-streaming commerce has become an important marketing channel of agricultural product, and it is also profoundly changing consumers’ online habits, spiritual, and cultural needs. This paper investigates the influencing factors of channel choice toward agricultural products under the live-streaming commerce, by developing a conceptual model among single-channel shopping cost, reference groups, positive online reviews, single-channel perceived risk, perceived value, and purchase intention. This article conducts a questionnaire survey on 591 samples in China. The results show that single-channel shopping cost, reference groups, positive online reviews, and perceived benefit have a significant positive impact on the omni-channel purchase intention of agricultural products, and perceived value plays a mediating role. Moreover, contextual factors partially have a negative moderating effect. When consumers purchase agricultural products, the more suitable the online shopping environment is, the weaker the influence of single-channel shopping costs, reference groups and positive online reviews on consumers’ omni-channel purchase intention of agricultural products. The findings may shed lights on how to promote the healthy development of the omni-channel sales model of agricultural products.